2017
DOI: 10.18632/oncotarget.20320
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of Chinese herbal injections combined with the FOLFOX regimen for treating gastric cancer in China: a network meta-analysis

Abstract: BackgroundChinese herbal injections (CHIs) have been proven beneficial to patients with gastric cancer for improving clinical efficacy and relieving adverse reactions (ADRs) of chemotherapy. A network meta-analysis (NMA) was conducted in this study to assess the comparative efficacy and safety of CHIs combined with FOLFOX regimen for treating gastric cancer.ResultsA total of 2316 records were searched, and 81 eligible RCTs involving 15 types of CHIs and 5978 patients were included in the NMA. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 34 publications
0
53
0
Order By: Relevance
“…Cinobufacini, a TCM preparation with antitumor and antiinflammation activity, has a good record of clinical efficacy and safety (Meng et al, 2012;Zhang et al, 2017a). In the practice of TCM therapeutics, cinobufacini is also commonly used as a drug to treat acute and chronic colitis, but no clinical or experimental research has been officially reported.…”
Section: Discussionmentioning
confidence: 99%
“…Cinobufacini, a TCM preparation with antitumor and antiinflammation activity, has a good record of clinical efficacy and safety (Meng et al, 2012;Zhang et al, 2017a). In the practice of TCM therapeutics, cinobufacini is also commonly used as a drug to treat acute and chronic colitis, but no clinical or experimental research has been officially reported.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed the effectiveness of CKI in the treatment of GC [20,21] but did not explore the molecular biology. To better analyze and predict the molecular mechanism of CKI in the treatment of GC, this study adopted the network pharmacology and molecular docking method.…”
Section: Introductionmentioning
confidence: 98%
“…Besides, it has passed the standardized Good Manufacturing Process (GMP) certi cation and is often used clinically to treat gastric cancer [9]. After multiple systematic reviews and meta-analysis studies, it was found that CKI can not only improve the clinical e cacy of gastric cancer patients but also alleviate the adverse effects of radiotherapy and chemotherapy [48][49][50]. Cancer is a complex disease arising from changes in multiple biological networks [51].…”
Section: Discussionmentioning
confidence: 99%